Psychoeducational program for the appropriate use of social networks in Cuban university students - Martínez, Anneidy Lamadrid; Castillo, Evelyn Fernández; Nápoles, Dayessi Riverón; García, Anna Hernández; Placeres, Grizly Meneses; Peralta-González, María Josefa; Anido, Anagret Mederos; Hurtado, Anabel Díaz (AWARI, 2023)
This article presents the basis of a psychoeducational program that promotes Cuban university students' responsible use of social networks. A mixed paradigm was used, and a retrospective ex-post-facto design and a descriptive scope were assumed. 30 university students participated in the design of the proposal. Instruments were used to collect the data, such as the questionnaire to evaluate protective factors of mental health in university students, the social network addiction questionnaire, and the survey to explore patterns of use of social networks. Descriptive and frequency analysis was used to analyze the data. Reviewing the studies conducted in the Cuban university context and the diagnosis developed in the selected sample allowed us to verify that students present difficulties developing social skills. However, a statistically significant relationship between the protective factors of mental health explored and the addictive indicators regarding the use of social networks is not confirmed from a statistical point of view. The triangulation of the information obtained allowed the design of a psychoeducational intervention to promote the appropriate use of social networks, consisting of four sessions based on the health belief model.